Acid- and Base-Induced Proteins during Aerobic and Anaerobic Growth of Escherichia coli Revealed by Two-Dimensional Gel Electrophoresis - Blankenhorn, Darcy (American Society for Microbiology, 1999)
Proteins induced by acid or base, during long-term aerobic or anaerobic growth in complex medium, were identified in Escherichia coli. Two-dimensional gel electrophoresis revealed pH-dependent induction of 18 proteins, nine of which were identified by N-terminal sequencing. At pH 9, tryptophan deaminase (TnaA) was induced to a high level, becoming one of the most abundant proteins observed. TnaA may reverse alkalinization by metabolizing amino acids to produce acidic products. Also induced at high pH, but only in anaerobiosis, was glutamate decarboxylase (GadA). The gad system (GadA/GadBC) neutralizes acidity and enhances survival in extreme acid; its induction during anaerobic growth may help protect alkaline-grown cells from the acidification resulting from anaerobic fermentation. To investigate possible responses to internal acidification, cultures were grown in propionate, a membrane-permeant weak acid which acidifies the cytoplasm. YfiD, a homologue of pyruvate formate lyase, was induced to high levels at pH 4.4 and induced twofold more by propionate at pH 6; both of these conditions cause internal acidification. At neutral or alkaline pH, YfiD was virtually absent. YfiD is therefore a strong candidate for response to internal acidification. Acid or propionate also increased the expression of alkyl hydroperoxide reductase (AhpC) but only during aerobic growth. At neutral or high pH, AhpC showed no significant difference between aerobic and anaerobic growth. The increase of AhpC in acid may help protect the cell from the greater concentrations of oxidizing intermediates at low pH. Isocitrate lyase (AceA) was induced by oxygen across the pH range but showed substantially greater induction in acid or in base than at pH 7. Additional responses observed included the induction of MalE at high pH and induction of several enzymes of sugar metabolism at low pH: the phosphotransferase system components ManX and PtsH and the galactitol fermentation enzyme GatY. Overall, our results indicate complex relationships between pH and oxygen and a novel permeant acid-inducible gene, YfiD.